Statistical Skills Analysis of Students Using Online-Learning Platforms such as Whatsapp, Youtube, and Zoom Meetings during Covid-19 Pandemic - Bina, Nuraini Sri; Ramadhani, Rahmi; Andhany, Ella; Wardani, Hizmi (Universitas Muhammadiyah Mataram, 2021)
Education as a result of the Covid-19 pandemic has undergone transformation related to the learning process from face-to-face learning process to online-based learning process that utilizes various online platforms, such as WhatsApp, YouTube, and Zoom Meetings. The use of online platforms helps students to improve their cognitive skills, one of which is statistical skills. This study aims to determine whether there is a significant statistical difference between learning using WhatsApp, YouTube, and Zoom Meetings during online learning and to find out which online platforms are effective and interactive. The research sample consisted of 69 students taking statistics courses. The research method is mix-method or mix of quantitative and qualitative. The data collection techniques are online-based test instruments, questionnaires and interviews. The data analysis used Kruskal Wallis test and descriptive analysis test. The results showed that there were differences in students' statistical skills between the three classes, where the best came from learning using YouTube platform. The findings also show that students give higher positive responses to the use of YouTube as platform in online learning. The interview results show that the use of YouTube is more effective and interactive for students while participating in online-based learning. By that means, YouTube platform is effective in improving statistical skills in online learning.